A Numerical Study for Dielectronic Recombination Processes in He-Like Argon (Communications in Computational Physics, 2007)
Ab initio calculations of dielectronic recombination (DR) processes from theground state 1s2 of He-like argon ion through doubly excited states 1s2snl, 1s2pnl(n=2 to 9) of Li-like argon ions are performed using the multi-configuration Hatree-Fock method with relativistic correction. The theoretical method and its correspondingcomputation will be outlined. For higher doubly excited states with n>9, the scalinglaw is used to extrapolate the Auger and radiative transition rates. The total and state-to-state cross sections with corresponding rate coefficients in the temperature from 102eV to 106eV are presented, as well as the DR strengths for all the separate resonances.Moreover, peculiarities of the DR from doubly excited 1s2s3l ' configurations are analyzed and the contributions of two-electron-one-photo (TEOP) radiative transitions tothe DR cross sections are also investigated, such as 1s2s2 → 1s22p, due to the strongconfiguration interactions. Our theoretical results appear to be in excellent agreementwith the previous and recent experimental measurements.